Capacity building for post‐disaster infrastructure development and management - Haigh, Richard; Amaratunga, Dilanthi (International Journal of Strategic Property Management, 2009)
„Capacity building for post‐disaster infrastructure development and management"International Journal of Strategic Property Management, 13(2), p. 83-86First Publish Online: 18 Oct 2010